Identification of Long Noncoding RNAs lnc-DC in Plasma as a New Biomarker for Primary Sjögren's Syndrome. (16th October 2020) - Chen, Yanhong; Chen, Yongqiang; Zu, Beibei; Liu, Jia; Sun, Li; Ding, Chen; Wang, Duping; Cheng, Xing; Yang, DeLiang; Niu, Guoping
Abstract : Objective . To evaluate the plasma levels of lnc-DC in primary Sjögren's syndrome (pSS) patients and investigate the potential associations between lnc-DC and disease activity. Methods . In this study, we recruited 358 enrollments, including 127 pSS patients without immune thrombocytopenia (ITP), 22 pSS patients with ITP, 50 systemic lupus erythematosus (SLE) patients, and 50 patients with rheumatoid arthritis (RA) and 109 healthy individuals, from Xuzhou Central Hospital. The expression of anti-SSA and anti-SSB was detected by enzyme-linked immunosorbent assay (ELISA). Spearman rank correlation test was used to analyze the relationship between lnc-DC and pSS activity. pSS activity was measured by anti-SSA, anti-SSB antibody, erythrocyte sedimentation rate (ESR), and β 2 -microglobulin levels. The receiver operating characteristic (ROC) curve was used to determine the diagnostic performance of plasma lnc-DC for pSS. Results . Compared with healthy controls, SLE and RA patients, the lnc-DC expression levels were significantly elevated in pSS patients (P < 0.001 ), especially in pSS patients with ITP (P < 0.001 ). As expected, we also found that the lnc-DC expression positively correlated with anti-SSA (R 2 = 0.290, P < 0.001 ), anti-SSB (R 2 = 0.172, P < 0.001 ), ESR level (R 2 = 0.076, P = 0.002 ), and β 2 -microglobulin level (R 2 = 0.070, P = 0.003 ) in pSS patients. ROC curves showed that plasma lnc-DC in pSS patients had an AUC 0.80 with a sensitivity of 0.75 and specificity of 0.85 at the optimum cutoff 1.06 in discriminating SLE and RA patients. In addition, the combination of lnc-DC and anti-SSA/SSB (AUC: 0.84, sensitivity: 0.79, specificity: 0.90) improved significantly the diagnostic ability of pSS patients from SLE and RA patients. In the efficacy monitoring study, levels of plasma lnc-DC were dramatically decreased after treatment (P < 0.001 ). Conclusion . These findings highlight that plasma lnc-DC as a novel biomarker for the diagnosis of pSS and can be used to evaluate the therapeutic efficacy of pSS underwent interventional therapy.